PERANAN ROH KUDUS DAN RELEVANSINYA PADA KEHIDUPAN PELAYANAN RASUL PETRUS - Liman, Vincentius (Sekolah Tinggi Teologi Injili Abdi Allah, 2020)
AbstracThe purpose of this writing is to prove that the Holy Spirit who is a person of the Triune God plays an active role and works in the Apostles, especially in the life of the Apostle Peter. However, it should not be understood that the Holy Spirit only worked on the Apostle Peter. The doctrine of the Holy Spirit as the Person of God is very important of the Apostle Peter's ministry call to the end of his life, with the aim of knowing and identifying the role of the Holy Spirit in the life of the Apostle Peter to understand where all God's Work is fulfilled through the Holy Spirit, in other words the Holy Spirit is the executor of all God's work. Especially after the ascension of Christ Jesus to Heaven, the Holy Spirit was poured out and played an active role in the life of the Apostle Peter. The role of the Holy Spirit is so clearly seen in the life of the Apostle Peter, the Holy Spirit accompanied the Apostle Peter in his ministry, not only accompanying Him but even transforming the life of the Apostle Peter. What a tremendous change occurred in the life of the Apostle Peter. The author describes how the early life.Keyword : Holy Spirit, Ministry Life, Transformation, Apostle Peter.Abstrak - Tujuan Penulisan ini adalah membuktikan bahwa Roh Kudus yang adalah satu pribadi dari Allah Tritunggal berperan Aktif dan berkarya dalam diri para Rasul, khususnya dalam kehidupan pelayanan Rasul Petrus. Namun hal ini tidak boleh dipahami bahwa Roh Kudus hanya berkarya pada Rasul Petrus saja. Doktrin mengenai Roh Kudus sebagai Pribadi Allah sangatlah penting untuk dipahami dimana semua Pekerjaan Allah tergenapi melalui Roh Kudus, dengan kata lain Roh Kudus adalah pelaksana dari semua pekerjaan Allah. Khususnya setalah kenaikan Kristus Yesus ke Sorga, Roh Kudus dicurahkan dan berperan aktif pada kehidupan pelayanan Rasul Petrus. Peranan Roh Kudus itu begitu jelas terlihat dalam kehidupan Rasul Petrus, Roh Kudus menyertai Rasul Petrus dalam Pelayanannya, tidak hanya menyertai Dia bahkan mentransformasi Kehidupan Rasul Petrus. Sungguh sebuah perubahan yang sangat luar biasa terjadi dalam kehidupan Rasul Petrus. Penulis memaparkan bagaimana awal kehidupan panggilan pelayanan Rasul Petrus hingga akhir hidupnya, dengan tujuan mengetahui dan mengidentifikasikan adanya peran Roh Kudus dalam kehidupan Rasul Petrus.Kata Kunci : Roh Kudus, Kehidupan Pelayanan, Transformasi, Rasul Petrus.